Effectivity of speech valves as a speech aid for cleft palate individuals - Guevara, Ma. Paz R.
This study was done to determine whether the use of a speech valve will enable cleft palate individuals to speak intelligibly. Eight subjects with palatal clefts were randomly selected from various sources. Subjects were asked to read a given material with a without a speech valve and recorded accordingly. Afterwhich the subjects were asked to undergo speech therapy to further enhance the effectivity of speech valve. Analysis of the results show that there is improvement of speech with the use of speech valve.